Socio-economic, land use and value chain perspectives on vanilla farming in the SAVA Region (north-eastern Madagascar): The Diversity Turn Baseline Study (DTBS) - Hendrik Hänke; Jan Barkmann; Lloyd Blum; Yvonne Franke; Dominic A. Martin; Jasnna Niens; Kristina Osen; Viviana Uruena; S. Annette Witherspoon; Annemarie Wurz (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
The SAVA Region in north-eastern Madagascar is the global centre of vanilla production. Here, around 70,000 farmers are estimated to produce 70-80% of all global bourbon vanilla. Yet, little is known about the farming population, their livelihoods, and the impact of vanilla cultivation on biodiversity. This publication presents the results of the Diversity Turn Baseline Survey (DTBS) that was conducted in 2017. The survey provides baseline data on the socio-economic characteristics and living conditions of the local population, and farming of vanilla as well as the most important other crops (n=1,800 households). As international demand for natural vanilla has increased considerably, special emphasis is placed on the vertical integration of vanilla farmers into the global vanilla value chain. This integration is increasingly accomplished through contract farming arrangements between vanilla farmers, collectors and exporters. After a first rise in vanilla prices in 2015, the current vanilla boom took off in 2016 and was still in full swing in 2017. Consequently, the start of the price boom coincides with this survey and its retrospective questions often address the situation in 2016. The large majority of the surveyed households (HHs) in the study region practice vanilla farming (83%). Of these, only 15% conclude formal contracts while the majority of farmers (63%) sell their vanilla in informal spot markets often depending on several middlemen. Our data show that the socio-economic situation of smallholder vanilla farmers has recently improved when considering vanilla prices received, education, access to electricity and ownership of assets. However, under the high vanilla prices, theft and crime are now key constraints for vanilla farmers. In addition to descriptive statistics, this publication compares selected data between male- and female-headed HHs, poor and non-poor HHs, and HHs with- and without contracts. Members of female-headed HHs have significantly lower education, lower labour availability, smaller fields and lower vanilla harvests than male-headed HHs. HHs with contracts possess more assets, are better educated, have higher labour availability, larger vanilla plots, and larger vanilla harvests than HHs without contracts. The DTBS confirms a number of benefits for smallholders who conclude contracts with vanilla exporters or collectors. Among these benefits are the significantly higher vanilla prices even during market peaks. However, the distribution of HHs with or without contracts is skewed indicating entry barriers for certain groups of smallholders. For example, female-headed HHs were significantly less likely to have a contract than male-headed HHs, and it appears that HHs with a contract had already been less poor than HHs without a contract prior to entering contract arrangements.
Keywords: 330